2020
DOI: 10.1111/cge.13772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in type 2 diabetes: A promising approach toward a personalized management of diabetes

Abstract: Diabetes mellitus, also known simply as diabetes, has been described as a chronic and complex endocrine metabolic disorder that is a leading cause of death across the globe. It is considered a key public health problem worldwide and one of four important non-communicable diseases prioritized for intervention through world health campaigns by various international foundations. Among its four categories, Type 2 diabetes (T2D) is the commonest form of diabetes accounting for over 90% of worldwide cases. Unlike mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 306 publications
(595 reference statements)
0
23
0
Order By: Relevance
“…In combination with our results showing that none of the scores tested nor diabetes duration alone can be used to correctly identify those who will achieve durable remission, these results suggest that preoperative prediction models need to be improved before being used for overall prediction of long-term diabetes outcomes. The etiology of type 2 diabetes is complex, and factors such as genetic predisposition to reduced insulin secretion or impaired b-cell function, control systems for maintaining energy balance, or psychological or behavioral characteristics may need to be considered in future prediction models to improve clinical utility (36)(37)(38). It is possible that an extended approach that includes such factors could identify patients with a low chance of remission, enabling targeted intensified postoperative management to optimize postsurgery weight reduction and long-term glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with our results showing that none of the scores tested nor diabetes duration alone can be used to correctly identify those who will achieve durable remission, these results suggest that preoperative prediction models need to be improved before being used for overall prediction of long-term diabetes outcomes. The etiology of type 2 diabetes is complex, and factors such as genetic predisposition to reduced insulin secretion or impaired b-cell function, control systems for maintaining energy balance, or psychological or behavioral characteristics may need to be considered in future prediction models to improve clinical utility (36)(37)(38). It is possible that an extended approach that includes such factors could identify patients with a low chance of remission, enabling targeted intensified postoperative management to optimize postsurgery weight reduction and long-term glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Precision DM medicine promises to be useful in customized therapy for those suffering from different types of diabetes, such as T2DM. 127 T2DM is a polygenic condition, and the clinical phenotype reflects both genetic and environmental effects, making it far more challenging to define subgroups using molecular testing. 128 One strategy for precision medicine in T2DM is to divide patients into subgroups based on treatment response and then examine the biological underpinnings of each subgroup utilizing next-generation sequencing platforms and gene arrays.…”
Section: Dovepressmentioning
confidence: 99%
“…T2D and its complications have reached the level of an epidemic, which has attracted great attention in the field of scientific research [ 1 ]. A number of studies have confirmed that T2D is a complex disease affected by multiple factors and is the result of the interaction between genes and the environment [ 1 4 ]. Evidence from genetic epidemiology indicates that the occurrence of type 2 diabetes has a strong genetic basis [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%